Quaternized chitosan-based composite membrane material and its preparation method and application
By combining quaternized chitosan with crosslinking agent and two-dimensional layered material, a quaternized chitosan-based composite film material with high power density was prepared, which solved the problem of large-area preparation of nanochannel membrane materials in the prior art and the complex process, and realized a high-performance membrane material suitable for osmotic energy generation.
Patent Information
- Application Number
- CN202411640003.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The prior art is difficult to prepare nanochannel film materials with high power density on a large area, and the preparation process is complicated.
By dissolving quaternized chitosan and crosslinking agent in an organic solvent, a mixed solution is formed, and after drying the surface of the matrix material, a two-dimensional layered material suspension is poured onto the surface of the chitosan film and dried, and finally a quaternized chitosan-based composite film material is prepared.
A flexible film with a high power density (up to 13.6W/m2) has been prepared on a large area. The film has selective permeability to ions and is suitable for osmotic energy generation.
Smart Images

Figure CN119139930B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material preparation, in particular to a quaternized chitosan-based composite membrane material and a preparation method and application thereof. Background Art
[0002] Self-generation technology through membrane ion rectification characteristics is an emerging electrochemical energy conversion technology that relies on the migration of ions through the membrane in an asymmetric environment to generate a potential difference. That is, in electrolyte solutions of different concentrations, ions will spontaneously diffuse from high-concentration areas to low-concentration areas. Through specially designed membranes, especially membranes with selective ion channels or nanopore structures, directional migration of specific ions can be achieved. Due to the rectification characteristics of the membrane, that is, it has asymmetry for the passage of ions, it can allow ions to pass more easily in a certain direction, but is restricted in the opposite direction. This unidirectional ion flow generates a transmembrane potential, thereby driving the electron flow to generate electrical energy. With the development of nanotechnology, materials science and electrochemical technology, ion rectification characteristics self-generation technology will continue to improve its energy conversion efficiency and become an important research direction in the future field of green energy and micro energy. Common preparation methods include chemical etching, ion beam engraving, template method, electrochemical etching, etc., but nanochannels are difficult to prepare on a large scale due to their small size, difficulty in regulation, and complex preparation process. Summary of the invention
[0003] Based on the above content, the present invention provides a quaternized chitosan-based composite membrane material and a preparation method and application thereof. By this method, a flexible film with high power density can be prepared. The film has selective permeability to ions, similar to a solid diode, and the film thickness is between 0.08-0.11 mm. The preparation method is simple to operate and can be prepared on a large area.
[0004] To achieve the above object, the present invention provides the following solutions:
[0005] One of the technical solutions of the present invention is a method for preparing a quaternized chitosan-based composite membrane material, comprising the following steps:
[0006] dissolving quaternized chitosan and a cross-linking agent in an organic solvent to obtain a mixed solution;
[0007] pouring the mixed solution onto the surface of the base material and drying it to obtain a chitosan film;
[0008] pouring a two-dimensional layered material suspension onto the surface of the chitosan membrane, and drying to obtain the quaternized chitosan-based composite membrane material;
[0009] The crosslinking agent is polyvinylidene fluoride, acrylic acid or vinyl acetate.
[0010] The second technical solution of the present invention is a quaternized chitosan-based composite membrane material prepared by the above-mentioned preparation method.
[0011] The third technical solution of the present invention is the application of the above-mentioned quaternized chitosan-based composite membrane material in osmotic energy power generation.
[0012] The present invention discloses the following technical effects:
[0013] The invention provides a method for preparing a quaternary ammonium chitosan-based composite membrane material. The preparation method is simple, has good stability, and can be prepared on a large scale.
[0014] The quaternized chitosan-based composite membrane material prepared by the method of the present invention has a high power density (up to 13.6 W / m 2 ), the film has selective permeability to ions, similar to a solid diode, and the film thickness is between 0.08-0.11mm.
[0015] The quaternized chitosan-based composite membrane material of the present invention can be applied to osmotic energy power generation. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 This is a cross-sectional SEM image of the QCS film (quaternized chitosan-based composite membrane material) prepared in Example 1 of the present invention;
[0018] Figure 2 This is a longitudinal cross-sectional SEM image of the QCS / MoS2-0.75 film prepared in Example 3 of the present invention;
[0019] Figure 3 Schematic diagram of the device for testing the electrochemical properties of the QCS / MoS2-0.75 film prepared in Example 3 of the present invention;
[0020] Figure 4 The ion rectification performance test results of the QCS / MoS2 composite membranes prepared in Examples 1-5 of the present invention;
[0021] Figure 5 The power density output by the QCS / MoS2-0.75 film prepared in Example 3 of the present invention under different concentration gradients;
[0022] Figure 6This is a diagram of the power density and current density output of the QCS / MoS2-0.75 film prepared in Example 3 of the present invention under a concentration difference of 50 times. DETAILED DESCRIPTION
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0024] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0028] As a natural bioactive substance, chitosan is considered to be a preferred material due to its non-toxicity, biocompatibility and low cost. The present invention prepares a membrane material by compounding quaternized chitosan with MoS2. After the quaternization reaction, the powerful -NH2 on the chitosan changes from N atoms to -N+(CH3)3 ions, which are easy to interact electrostatically with anions in the solution, and construct ion transmission channels with asymmetric charges in the membrane structure. Macroscopically, chitosan is compounded with molybdenum disulfide to form a heterojunction, and asymmetric ion transmission channels on both sides of the interface are constructed. Thereby further improving the ion selectivity of the film and higher concentration difference output power density and current density.
[0029] One of the technical solutions of the present invention is a method for preparing a quaternized chitosan-based composite membrane material, comprising the following steps:
[0030] dissolving quaternized chitosan and a cross-linking agent in an organic solvent to obtain a mixed solution;
[0031] pouring the mixed solution onto the surface of the base material and drying it to obtain a chitosan film;
[0032] pouring a two-dimensional layered material suspension onto the surface of the chitosan membrane, and drying to obtain the quaternized chitosan-based composite membrane material;
[0033] The crosslinking agent is polyvinylidene fluoride, acrylic acid or vinyl acetate.
[0034] In the present invention, stirring can be used to fully dissolve the quaternized chitosan and the crosslinking agent in the organic solvent to obtain a mixed solution; the present invention does not impose any particular limitation on the stirring rate, and the conventional stirring rate in the art can be used.
[0035] In some specific embodiments of the present invention, the quaternary ammonium chitosan and polyvinylidene fluoride are dissolved in the organic solvent by stirring for 20-24 hours to completely dissolve the quaternary ammonium chitosan and polyvinylidene fluoride in the organic solvent.
[0036] In a preferred embodiment of the present invention, the mass ratio of the quaternized chitosan to the cross-linking agent is (3-7):3.
[0037] The present invention does not specifically limit the source of quaternized chitosan, and commercially available products known to those skilled in the art can be used. The higher the degree of substitution of quaternized chitosan, the better the performance of the prepared membrane. Therefore, in some specific embodiments, quaternized chitosan with a higher degree of substitution (such as a degree of substitution of 98%) commercially available in the prior art can be used.
[0038] The reasons why the present invention limits the mass ratio of quaternized chitosan to polyvinylidene fluoride to the above ratio are as follows: if the amount of quaternized chitosan is too much, the quaternized sample will not be completely cross-linked, and powder sample will remain after drying; if the amount of quaternized chitosan is too little, the ion selectivity of the membrane will be reduced.
[0039] The present invention does not impose any particular limitation on the amount of the organic solvent used. The amount of the organic solvent used is sufficient to fully dissolve the quaternized chitosan and the polyvinylidene fluoride.
[0040] In some specific embodiments of the present invention, the mass volume ratio of the quaternized chitosan, polyvinylidene fluoride and organic solvent is 0.7g:0.3g:15mL.
[0041] In a preferred embodiment of the present invention, the mass ratio of quaternized chitosan to the two-dimensional layered material in the two-dimensional layered material suspension is 700:(0.5-2); the solvent of the two-dimensional layered material suspension is N-methyl-2-pyrrolidone; and the two-dimensional layered material is MoS2, WS2, BN, MoSe2, WSe2 or MXene.
[0042] In some specific embodiments of the present invention, taking MoS2 as an example, the MoS2 suspension is prepared by dissolving 0.5-2 mg MoS2 powder in 20 mL N-methyl-2-pyrrolidone and ultrasonicating for 1 h.
[0043] In some specific embodiments of the present invention, the volume ratio of the mixed solution to the MoS2 suspension is 3:4.
[0044] In a preferred embodiment of the present invention, the organic solvent is N-methyl-2-pyrrolidone. In some specific embodiments of the present invention, the purity of N-methyl-2-pyrrolidone is 90%.
[0045] In a preferred embodiment of the present invention, when preparing the chitosan film, the drying temperature is 80-85°C and the drying time is 18-24h; when preparing the quaternized chitosan-based composite membrane material, the drying temperature is 80-85°C and the drying is performed until the solvent is completely removed.
[0046] In some embodiments of the present invention, the time required for drying until the solvent is completely removed (complete drying) is 8-10 hours.
[0047] When preparing the quaternized chitosan-based composite membrane material, a step of washing with deionized water is also included after drying.
[0048] The second technical solution of the present invention is a quaternized chitosan-based composite membrane material prepared by the above-mentioned preparation method.
[0049] The third technical solution of the present invention is the application of the above-mentioned quaternized chitosan-based composite membrane material in osmotic energy power generation.
[0050] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0051] The quaternized chitosan used in the examples of the present invention was purchased from Guangdong Qianjin Chemical Reagent Co., Ltd., with the following main parameters: degree of substitution 98%, molecular weight 204.16.
[0052] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0053] Example 1
[0054] This embodiment provides a method for preparing a quaternary ammonium chitosan-based composite membrane material, the steps are as follows:
[0055] Step 1, weigh 0.7 g of quaternized chitosan sample and 0.3 g of polyvinylidene fluoride (PVDF) and dissolve them in 15 mL of N-methyl-2-pyrrolidone;
[0056] Step 2, the resulting solution was stirred continuously on a magnetic stirrer with a magnet at room temperature for 24 h;
[0057] Step 3, pour the stirred solution onto a smooth glass surface dish and dry it in a drying oven at 80°C for 20 h;
[0058] Step 4, peel off the dried film from the glass dish to obtain a complete film; marked as QCS, with a thickness of 0.106 mm.
[0059] Example 2
[0060] This embodiment provides a method for preparing a quaternary ammonium chitosan-based composite membrane material, the steps are as follows:
[0061] Step 1, weigh 0.7 g of quaternized chitosan and 0.3 g of polyvinylidene fluoride (PVDF) and dissolve them in 15 mL of N-methyl-2-pyrrolidone;
[0062] Step 2, the resulting solution was stirred continuously on a magnetic stirrer with a magnet at room temperature for 24 h;
[0063] Step 3, pour the stirred solution onto a smooth glass surface dish and dry it in a drying oven at 80°C for 20 h;
[0064] Step 4, weigh 0.5 mg MoS2 powder and ultrasonicate it in 20 mL N-methyl-2-pyrrolidone for 1 h;
[0065] Step 5, pouring the MoS2 suspension after ultrasonic treatment in step 4 onto the surface of the chitosan film prepared in step 3, and continuing to dry at 80°C until complete;
[0066] Step 6, peel off the dried film from the glass dish to obtain a complete film; marked as QCS / MoS2-0.5, with a thickness of 0.095 mm.
[0067] Example 3
[0068] This embodiment provides a method for preparing a quaternary ammonium chitosan-based composite membrane material, the steps are as follows:
[0069] Step 1, weigh 0.7 g of quaternized chitosan and 0.3 g of polyvinylidene fluoride (PVDF) and dissolve them in 15 mL of N-methyl-2-pyrrolidone;
[0070] Step 2, the resulting solution was stirred continuously on a magnetic stirrer with a magnet at room temperature for 24 h;
[0071] Step 3, pour the stirred solution onto a smooth glass surface dish and dry it in a drying oven at 80°C for 20 h;
[0072] Step 4, weigh 0.75 mg MoS2 powder and ultrasonicate it in 20 mL N-methyl-2-pyrrolidone for 1 h;
[0073] Step 5, pouring the MoS2 suspension after ultrasonic treatment in step 4 onto the surface of the chitosan film prepared in step 3, and continuing to dry at 80°C until complete;
[0074] Step 6, peel off the dried film from the glass dish to obtain a complete film; marked as QCS / MoS2-0.75, with a thickness of 0.097 mm.
[0075] Example 4
[0076] This embodiment provides a method for preparing a quaternary ammonium chitosan-based composite membrane material, the steps are as follows:
[0077] Step 1, weigh 0.7 g of quaternized chitosan and 0.3 g of polyvinylidene fluoride (PVDF) and dissolve them in 15 mL of N-methyl-2-pyrrolidone;
[0078] Step 2, the resulting solution was stirred continuously on a magnetic stirrer with a magnet at room temperature for 24 h;
[0079] Step 3, pour the stirred solution onto a smooth glass surface dish and dry it in a drying oven at 80°C for 20 h;
[0080] Step 4, weigh 1 mg of MoS2 powder and ultrasonicate it in 20 mL of N-methyl-2-pyrrolidone for 1 h;
[0081] Step 5, pouring the MoS2 suspension after ultrasonic treatment in step 4 onto the surface of the chitosan film prepared in step 3, and continuing to dry at 80°C until complete;
[0082] Step 6, peel off the dried film from the glass dish to obtain a complete film; marked as QCS / MoS2-1, with a thickness of 0.104 mm.
[0083] Example 5
[0084] This embodiment provides a method for preparing a quaternary ammonium chitosan-based composite membrane material, the steps are as follows:
[0085] Step 1, weigh 0.7 g of quaternized chitosan and 0.3 g of polyvinylidene fluoride (PVDF) and dissolve them in 15 mL of N-methyl-2-pyrrolidone;
[0086] Step 2, the resulting solution was stirred continuously on a magnetic stirrer with a magnet at room temperature for 24 h;
[0087] Step 3, pour the stirred solution onto a smooth glass surface dish and dry it in a drying oven at 80°C for 20 h;
[0088] Step 4, weigh 2 mg of MoS2 powder and ultrasonicate it in 20 mL of N-methyl-2-pyrrolidone for 1 h;
[0089] Step 5, pouring the MoS2 suspension after ultrasonic treatment in step 4 onto the surface of the chitosan film prepared in step 3, and continuing to dry at 80°C until complete;
[0090] Step 6, peel off the dried film from the glass dish to obtain a complete film; marked as QCS / MoS2-2, with a thickness of 0.088 mm.
[0091] The film obtained in the embodiment was characterized in morphology, and its rectification effect, power density and current density were tested. The test results are as follows:
[0092] 1. Morphological characterization of QCS / MoS2 composite films
[0093] Figure 1 This is a cross-sectional SEM image of the QCS film prepared in Example 1 of the present invention. Figure 2 This is the longitudinal cross-sectional SEM image of the QCS / MoS2-0.75 film prepared in Example 3 of the present invention. The heterogeneous structure of QCS / MoS2 can be clearly seen at a scale of 30 μm.
[0094] 2. Ion rectification test
[0095] Figure 4 The ion rectification performance test results of the quaternized chitosan-based composite membranes prepared in Examples 1-5 of the present invention; the film was fixed in the middle of an H-type electrolytic cell, and sodium chloride solutions (0.5M) of the same concentration were added to the electrolytic cells on both sides to test the transmembrane transport of ions in the sodium chloride solution between different quaternized chitosan-based composite membranes. The cyclic voltammetry method was used for testing using a four-electrode system, with a platinum wire as the working electrode and the counter electrode, a silver / silver chloride electrode as the sensing electrode and the reference electrode, a voltage window selected between -1 and +1, a scan rate of 50 mV / s, and a nonlinear current-voltage curve was measured. By Figure 4 It can be seen that the current under negative voltage is significantly greater than the current under positive voltage. By calculating the absolute value ratio of positive and negative currents, the ion selectivity of the quaternized chitosan-based composite membrane is evaluated (the larger the absolute value ratio of positive and negative currents, the better the ion selectivity). Figure 4 It can be seen that the addition of MoS2 effectively improves the ion selectivity of the composite membrane.
[0096] 3. Power density and current density test
[0097] Figure 3 Schematic diagram of the device for testing the electrochemical properties of the QCS / MoS2-0.75 film prepared in Example 3 of the present invention.
[0098] Figure 5 The power density output by the QCS / MoS2-0.75 membrane prepared in Example 3 of the present invention under different concentration gradients of sodium chloride solution is 5 times (5M / 1M), 50 times (5M / 0.1M), and 500 times (5M / 0.01M). It can be seen that the greater the concentration gradient, the greater the current density and power density output by the QCS / MoS2-0.75 membrane.
[0099] Figure 6 The power density and current density of the QCS / MoS2-0.75 membrane prepared in Example 3 of the present invention under a 50-fold concentration gradient (the concentrations of the sodium chloride solutions in the left and right electrolytic cells are 0.01M / 0.5M, respectively). Since the 50-fold concentration gradient is closest to the concentration gradient between seawater and fresh water, it has practical application value. It can be seen from the figure that the QCS / MoS2-0.75 membrane has a high output power density, which can reach 14.4W / m 2 .
[0100] Comparative Example 1
[0101] The only difference from Example 3 is that the addition of 0.7 g of quaternized chitosan is omitted, the addition amount of polyvinylidene fluoride is 1 g, and the remaining steps and parameters are the same as those in Example 3.
[0102] Results: The film prepared in this comparative example was subjected to the same effect verification as in Example 3. The results showed that its output power density at a concentration gradient of 50 times was 1.12 W / m 2 .
[0103] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a quaternized chitosan-based composite membrane material for osmotic energy generation, characterized in that: Here are the steps: dissolving quaternized chitosan and a cross-linking agent in an organic solvent to obtain a mixed solution; pouring the mixed solution onto the surface of the base material and drying it to obtain a chitosan film; pouring a two-dimensional layered material suspension onto the surface of the chitosan membrane, and drying to obtain the quaternized chitosan-based composite membrane material; The cross-linking agent is polyvinylidene fluoride; The mass ratio of the quaternized chitosan to the cross-linking agent is (3-7):3; The mass ratio of quaternized chitosan to the two-dimensional layered material in the two-dimensional layered material suspension is 700:(0.5-2); the two-dimensional layered material is MoS2; The organic solvent is N-methyl-2-pyrrolidone; When preparing the chitosan film, the drying temperature is 80-85°C and the drying time is 18-24h; when preparing the quaternized chitosan-based composite membrane material, the drying temperature is 80-85°C and the drying is performed until the solvent is completely removed; The thickness of the quaternized chitosan-based composite membrane material is between 0.08 mm and 0.11 mm.
2. The quaternized chitosan-based composite membrane material prepared by the preparation method according to claim 1.
3. Application of the quaternized chitosan-based composite membrane material as claimed in claim 2 in osmotic energy power generation.
Citation Information
Patent Citations
Film with ion rectification effect and high tensile property and preparation method thereof
CN117801348A
ENERGY PRODUCTION DEVICE USING SALINITY GRADIENTS THROUGH A CROSS-CUT CHITOSAN FIBER MEMBRANE
FR3129297A1